1999
DOI: 10.1063/1.124541
|View full text |Cite
|
Sign up to set email alerts
|

Large current density from carbon nanotube field emitters

Abstract: We observe that field emitters made from carbon nanotubes exhibit excellent macroscopic emission properties; they can operate at a very large current density, as high as 4 A/cm 2 . At electric fields as low as 4-7 V/m, they emit technologically useful current densities of 10 mA/cm 2 . We show that the emission originates from nanotube ends with a characteristic structured ring pattern. The emission characteristics and durability of the carbon nanotube cold cathodes offer promising applications for vacuum micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
260
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 552 publications
(270 citation statements)
references
References 18 publications
8
260
2
Order By: Relevance
“…Mass spectrometers usually require current levels in the 1-2 mA/cm 2 range (10 to 100 s of μA emitted from a filament). Many groups have shown that CNT field emitters are capable of emission current exceeding 10 mA/cm 2 [10][11][12], demonstrating they can provide sufficient electron emission current for MS. Turn-on fields for CNT field emitters are also very low, enabling low power operation. Wang et al reported turn-on fields as low as 0.64 V/μm at a current density of 10 μA/cm 2 from functionalized CNT structures [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometers usually require current levels in the 1-2 mA/cm 2 range (10 to 100 s of μA emitted from a filament). Many groups have shown that CNT field emitters are capable of emission current exceeding 10 mA/cm 2 [10][11][12], demonstrating they can provide sufficient electron emission current for MS. Turn-on fields for CNT field emitters are also very low, enabling low power operation. Wang et al reported turn-on fields as low as 0.64 V/μm at a current density of 10 μA/cm 2 from functionalized CNT structures [13].…”
Section: Introductionmentioning
confidence: 99%
“…Potential technical applications in the areas of molecular electronic devices [2][3][4][5][6], nanocomposites [7][8][9][10], electron field emission [11][12][13][14][15] have been proposed or explored. In addition, because of the nature of their structure and chemical bonding, carbon nanotubes 2 are also interesting 1D host materials for lithium intercalation, and several groups have already investigated the application of carbon nanotubes as the anode for lithium batteries [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have attracted much attention in recent years because of their unique electrical, mechanical, and various physical properties. [1][2][3][4][5][6][7][8] For many potential applications, aligned CNT geometry is important. It is well known that vertically aligned nanotube arrays can be grown by plasma-enhanced chemical vapor deposition (PECVD) processing, either microwave 9 or dc plasma.…”
mentioning
confidence: 99%